Development of a RAPD marker‐based classification criterion for quality semen production in Holstein crossbred bulls. Issue 5 (16th February 2021) - Hussain, Shaziya; Alex, Rani; Alyethodi, Rafeeque R.; Sharma, Shalini; Verma, Nitika; Sirohi, Ajayvir Singh; Singh, Umesh; Kumar, Sushil; Chand, Naimi; Sengar, Gyanendra S.; Sharma, Ankur; Tyagi, Rachna; et al.
Abstract: In cattle production systems, an intense selection pressure for production traits has resulted in the decline of fertility traits. To optimize an efficient reproduction system, the inclusion of both male and female fertility traits in the selection process is very much essential. RAPD (Random Amplified Polymorphic DNA) was developed as a molecular biology tool and has been extensively used, to study intra‐ and interspecific genetic diversity. The present study was undertaken to utilize RAPD primers to investigate the association between DNA markers and semen quality traits viz. Sperm concentration, total sperm count ejaculate and initial sperm motility and thereby to identify good/poor semen producers. DNA isolated from the blood samples of healthy bulls was subjected to RAPD‐PCR. The multiple regression analysis followed by independent t test was carried out to identify suitable markers. Based on the results, only 12 bands were identified as marker suitable for any of the quality trait. This includes, OPA2 ~ 760, OPA2 ~ 700, OPA6 ~ 1, 200, OPA9 ~ 400, OPA9 ~ 380, OPA12 ~ 970, OPA14 ~ 715, OPA14 ~ 605, OPA16 ~ 485, OPA17 ~ 860 and OPA18 ~ 480. Multiple regression analysis selected, OPA2 ~ 760 and OPA2 ~ 1, 750 for sperm concentration and OPA2 ~ 760, OPA2 ~ 700, OPA9 ~ 620, OPA4 ~ 670 and OPA18 ~ 1, 015 for total sperm count/ejaculate. But the t test revealed a significant association between OPA2 ~ 760 and total sperm count. Further, discriminant function analysis also identified this marker in the first step itself. The results of the present study can be exploited as a low‐cost alternative strategy for identification of good /poor semen producers in crossbred bulls at an early age.